Все мы грешные: роман / В. Г. Колычев - Колычев Владимир Григорьевич (Эксмо, 2004)
Экземпляры: ф.13 (2004) / Инвентарный номер: 48354 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: К 61 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44